Inequality and housing - Dewilde, Caroline; Waitkus, Nora (Handbook of Labor, Human Resources and Population Economics, 2024)
This chapter discusses recent developments in theory and research on housing and inequality. Housing-related inequalities have become a topic of public, political, and policy urgency. Its scientific discussion, however, remained isolated in internal debate among...